PENGARUH BRAND IMAGE DAN BRAND TRUST TERHADAP BRAND LOYALTY TEH BOTOL SOSRO Survei Konsumen Teh Botol Sosro di Food Court ITC Cempaka Mas, Jakarta timur - Rizan, Mohammad; Saidani, Basrah; Sari, Yusiyana (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2012)
The purposes of this research are: 1) To know the description of brand image and brand trust and the influence of them towards brand loyalty of Teh Botol Sosro. 2) To test empirically the influence of brand image towards brand loyalty of Teh Botol Sosro. 3) To test empirically the influence of brand trust towards brand loyalty of Teh Botol Sosro. 4) To test empirically the influence of brand image and brand trust simultaneously towards brand loyalty of Teh Botol Sosro. The analysis implemented in this research are descriptive and causal analysis. This research is taken 100 consumers of Teh Botol Sosro at the food court of ITC Cempaka Mas while data was collected by using questionnaire and processed using SPSS 16. The result shows that partially brand image has a positive and significant impact toward brand loyalty. Then, partially brand trust also has a positive and significant impact toward brand loyalty. Simultaneously, brand image and brand trust have a positive and significant impact toward brand loyalty. The empirical findings indicate that to create and improve the brand loyalty, Teh Botol Sosro need to consider brand image and brand trust because those factors shown to affect the level of job satisfaction. Keywords: Brand Image, Brand Trust, Brand Loyalty